THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND MENTAL HEALTH AMONG ADOLESCENTS IN SENIOR HIGH SCHOOLS IN BANDA ACEH CITY - Imelda; Misbahul Muna (International Medical Journal Corp. Ltd, 2026)
Adolescence is a period that is particularly vulnerable to mental health issues due to hormonal, physical, and psychosocial changes. If not properly managed, these changes and challenges may trigger emotional and mental health disorders among adolescents. One strategy to prevent or reduce the risk of mental health problems is engaging in regular physical activity. This study aimed to examine the relationship between physical activity and mental health among adolescents in senior high schools in Banda Aceh. This research employed a descriptive correlational method with a cross-sectional study design. The population consisted of all tenth-grade students at Senior High School 9 Banda Aceh, with a total sample of 154 students. Data were collected using the Physical Activity Questionnaire for Adolescents (PAQ-A) and the Mental Health Continuum-Short Form (MHC-SF). Data were analyzed using the Chi-Square test. The results showed a significant relationship between physical activity and adolescent mental health, with a p-value = 0.000. It is recommended that adolescents engage more actively in physical activities to maintain their mental well-being. In addition, support from parents and schools in providing environments that encourage physical activity is essential to promote adolescent mental health.